1991
DOI: 10.1007/bf00023792
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of wild emmer wheat to stem rust: Ecological, pathological and allozyme associations

Abstract: Seedling resistance to wheat stem rust was determined in populations of wild emmer wheat, Triticum dicoccoides, and characterized by means of ecological factors and allozyme genotypes . Reactions to wheat stem rust were studied in 102 single plant accessions of T. dicoccoides from ten populations by inoculation with Puccinia graminis tritici race 14, isolate GSR-739 . Six populations displayed different degrees of response polymorphism with reactions ranging from high resistance to complete susceptibility, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Much of the observed annual variation in overall infection intensity may be the result of stringent weather conditions necessary for growth of the fungal population. Nevo et al (1991) found that significant rust infection of wheat requires a minimum number of degree days with high humidity. These conditions were guaranteed for our potted plant surveys, both of which had high overall infection intensity, because regular watering kept their foliage damp.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the observed annual variation in overall infection intensity may be the result of stringent weather conditions necessary for growth of the fungal population. Nevo et al (1991) found that significant rust infection of wheat requires a minimum number of degree days with high humidity. These conditions were guaranteed for our potted plant surveys, both of which had high overall infection intensity, because regular watering kept their foliage damp.…”
Section: Discussionmentioning
confidence: 99%
“…Wild emmer wheat is an important genetic resource that could be exploited in breeding for resistance to a broad range of diseases, pests, and for tolerance to poor soil and climatic factors (Nevo 1983(Nevo , 1989(Nevo , 1995. Among many agriculturally important characteristics already found in T. dicoccoides is its resistance to stripe rust (Gerechter-Amitai and Stubbs 1970;Nevo et al 1986;Fahima et al 1998), stem rust (Nevo et al 1991), and powdery mildew (Nevo et al 1985). Wild emmer wheat contains rich and variable genetic resources that will play a major role in future wheat improvement (Nevo 1983(Nevo ,1989(Nevo , 1995.…”
Section: Org]mentioning
confidence: 99%
“…(1) central (2) xeric marginal (# 16-23) and (3) mesic marginal (# 24-33) . The xeric locations were further subdivided into xeric warm marginal, eastern and southern on the basis of meteorological records (see Nevo & Beiles, 1989 ;Nevo et al ., 1991) .…”
Section: Host Populationsmentioning
confidence: 99%